Service quality (SERVQUAL) influence customer satisfaction of Tampin Perodua Service Centre / Syahirah Aisyah Mohd Zafri - Mohd Zafri, Syahirah Aisyah (Faculty of Business and Management, 2019)
Service quality seems to be accepted as a fundamental factor that will influence customer satisfaction towards service centre. However, it has been ignored regarding on the matter of service quality on customer satisfaction studies. The primary objective of this study was to investigate how service quality (SERVQUAL) can influence customer satisfaction on Tampin Perodua service centre. Subsequent regression analyses demonstrated that service quality (SERVQUAL) influence customer satisfaction through the quality of service that they serve to their customers. Thus, the manager should pay attention to the dimensions of service quality (SERVQUAL) that elicit customer satisfaction and enhance return visits to the service centre. This study was developed to investigate on how service quality (SERVQUAL) can influence customer satisfaction on Tampin Perodua service centre. Tangible, reliability, responsiveness, assurance and empathy are the factors that used to influence customer satisfaction towards the service centre in Tampin, Negeri Sembilan. The survey was conducted to gather the data and 310 respondents had answered the questionnaire. Data analysis was then based on the 310 valid responses. The findings would be useful to help automobile service centre to make improvements. The conclusion of the result is that responsiveness, assurance and empathy have significant relationship with customer satisfaction.